Influence of the Bcg locus on macrophage response to the dimorphic fungus Candida albicans. - Puliti, M (1995)
The Bcg/Ity/Lsh gene (candidate Nramp) controls natural resistance to several parasites, such as Mycobacterium bovis, Leishmania donovani, and Salmonella typhimurium. Using two macrophage (M phi) cell lines (B10R and B10S) derived from mouse strains congenic at Bcg, we found that M phi s from resistant mice (B10R M phi s) act more effectively against the two morphogenetic forms of the dimorphic fungus Candida albicans compared with M phi s from susceptible mice (B10S M phi s). Moreover, when assessed for tumor necrosis factor secretion in response to the hyphal form of C. albicans, B10R M phi s are significantly more effective at expressing this secretory function than are B10S M phi s, closely resembling the trend of response to lipopolysaccharide. Overall, these results provide insight into the influence of the Bcg locus on the M phi response to C. albicans.